A chitosan-based nano-formulation with higher biological efficacy and lower toxicity for sustainable release of carbendazim in the soils under Crocus sativus L. cultivation - ANAND, RYTHEM; SHARMA, ANIL; BHAGAT, MADHULIKA (Journal of Soil and Water Conservation, 2025)
The overuse of conventional pesticides has raised environmental concerns and lowered soil health requiring sustainable alternatives must be developed. In this study, a chitosan-based nano-formulation for the regulated release of carbendazim, a common fungicide, used in Crocus sativus L. (saffron) cultivation is synthesized followed by their characterisation. The nano-formulation formed using the ionic gelation method, exhibited a size of 184.8 nm with an irregular morphology and their antifungal activity was observed against Fusarium oxysporum showing 81.8% inhibition. The findings showed that nanoscale particles had a high encapsulation efficiency, guaranteeing the regulated and extended release of carbendazim in the soil. The nano-formulation demonstrated enhanced biodegradability and decreased toxicity to non-target organisms, such as soil microbes. Additionally, the chitosan matrix reduced pesticide runoff and leaching while enriching the soil with organic content, decreasing environmental contamination. The effect of nano-formulation of carbendazim on soil parameters of Crocus sativus such as pH, electrical conductivity (EC), organic carbon (OC), moisture, presence of metals like Zn, Fe, Mn and Cu, flower length, flower diameter, fresh weight, dry weight, stamen + stigma exhibited an increase as compared to the control. This approach provides a promising alternative for the development of ecofriendly agricultural practices.